"Biomasa y composicion quimica de cuatro variedades de briachiarias en tres estados fenologicos en el Canton El Empalme Provinvia del Guayas, Ecuador 2013". - Zambrano Molina, José Luis (2015)
This research was conducted in the province of Guayas, El Empalme, Organization Limón de Manizales. The investigation lasted six months (November 2012 to May 2013). Aimed to evaluate the effect of three cutting ages on forage biomass and chemical composition of four varieties of Brachiarias. An experimental design of plots Split randomized complete block with a factorial arrangement was employed 4 x 3 (4 types of grasses: Brachiaria decumbens, Brachiaria mulatto, Brachiaria brizantha, Brachiaria Xaraes and three cutting ages 30, 45 and 60 days). The variety with the highest average production of forage biomass (kg ha-1) fresh and dry matter was Brachiaria brizantha. It was determined that production of fresh forage biomass (FV) and dry matter (DM) increases as age increases cutting, having increased production to 60 days. Brachiaria brizantha acceptable parameters reported chemical composition, having a lower content (%) of crude fiber (CF) (27.84) and higher presence of ash (15.25), relative to the other varieties tested. Brachiaria decumbens showed the highest values (%) of crude protein (CP) (11.10) and crude fiber (CF) (30.53). The percentage of dry matter (DM) was higher for Brachiaria Xaraes (27.10), this variety also reported the highest fat content (1.42%). The percentage of dry matter, protein and fat was higher in the age of 30 days, decreasing as the age increases, while the ash content and crude fiber had an opposite trend, increasing with increasing age. The mineral content was similar in B. decumbens, B. and B. Brizantha mulatto, while B. Xaraes reported the lowest except for the content (ppm) of manganese averages. The content of calcium, magnesium (%), copper, manganese and zinc (ppm) decreased as age progressed. Opposite to what reported the percentage of potassium increased for age. Phosphorus (%) and iron (%) were above 45 days. Keywords: Brachiarias, forage biomass, harvest age.